2021
DOI: 10.30918/aerj.91.20.205
|View full text |Cite
|
Sign up to set email alerts
|

The effect of realistic mathematics education on student achievement in 8th grades geometric objects teaching

Abstract: The purpose of this study is to answer if there is a reasonable difference on academical success of students who get education with traditional and RME approach question on “Teaching geometrical objects to 8th grade students” subject. Study group consists of 47 students which contains 21 experimental and 16 control group from “Ordu Anadolu İmam Hatip High School Project School” in Altinordu, Ordu. Experimental and control group have same academical success level, as the school which this study has runned is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A flipped classroom is one of the technology-based teaching instructional techniques whereby teachers record lessons for students to learn on their own and use the class hours for discussions and problem-solving (Atta & Asiedu-Addo, 2021;Arfiana & Wijaya, 2018). Studies have demonstrated that Flipped classroom offers students the opportunity to learn actively and at their own pace (Abeysekera & Dawson, 2015;Aksu & Colak, 2021;Akuffo et al, 2019;Atta & Brantuo, 2021). As pre-service teachers, there is a need for them to appreciate the concept of plane geometry well to impart it to the future leaders of the country, hence the need for this study.…”
Section: Geometry and The Flipped Classroom Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…A flipped classroom is one of the technology-based teaching instructional techniques whereby teachers record lessons for students to learn on their own and use the class hours for discussions and problem-solving (Atta & Asiedu-Addo, 2021;Arfiana & Wijaya, 2018). Studies have demonstrated that Flipped classroom offers students the opportunity to learn actively and at their own pace (Abeysekera & Dawson, 2015;Aksu & Colak, 2021;Akuffo et al, 2019;Atta & Brantuo, 2021). As pre-service teachers, there is a need for them to appreciate the concept of plane geometry well to impart it to the future leaders of the country, hence the need for this study.…”
Section: Geometry and The Flipped Classroom Approachmentioning
confidence: 99%
“…One of the areas of mathematics that remains a challenge in primary schools is geometry. Most of the studies in this area have also focused on students, especially in secondary school (Aksu & Colak, 2021;Uwurukundo et al, 2022). However, not many studies have been done focusing on pre-service teachers being trained for the primary schools; the present study, therefore, seeks to bring to light the need to enhance the content knowledge of the pre-service teachers for effective delivery.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Studies have shown that the focus of school mathematics has been on for decades in several countries. Realistic Mathematics Education (RME) was primarily borne out of problemsolving (Aksu & Colak, 2021;Arsaythamby & Zubainur, 2014) and has become a household name in mathematics education. Most of the best-performing countries in the TIMSS assessment project have reviewed their mathematics curriculum to absorb the RME (Mullis et al, 2012) The constructivist theory of learning also links with Bloom's taxonomy since the theory aims to enhance students' knowledge creation based on their previous experience (Adom et al, 2016).…”
Section: The Psychomotor Domainmentioning
confidence: 99%
“…Teaching mathematics in context promotes growth by teaching pupils about their country's values, ideals, history, and culture. Researchers like Aksu and Colak (2021), Huinker (2018), and Kepner (1974) observed that, China, Finland, the United States, and United Kingdom, among others have developed, partly as a result of their contextual mathematics instruction. Since mathematics is used worldwide for national development, several research are being carried out periodically to keep the teaching of school mathematics abreast with time (Japelj Pavesic et al, 2022;Rizqika & Shofyan, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have proposed pedagogies to improve pre-tertiary mathematics teaching. Among them are critical pedagogy (Freire, 2020a;Giroux, 2020), mathematics for social justice (Stinson et al, 2012), realistic mathematics education (Barnes, 2005;Rizqika & Shofyan, 2021), problem-solving approach (Aksu & Colak, 2021;Turgut, 2021), and others. These mathematical learning methods promote inquiry, problem-solving, critical thinking, and investigation.…”
Section: Introductionmentioning
confidence: 99%